The City in a Different Way: Space in the Essay “Rational Decisions” by Giedra Radvilavičiūtė - Vidugirytė, Inga (Semiotika, 2024)
The article deals with the writing/production of space in Giedra Radvilavičiūtė’s essay “Rational Decisions”. In contemporary (literary) geography, the writing of space presupposes that space is perceived not as an empty container/stage where the action takes place, but as the space of relationships and networks of human and non-human characters which create the relational space or space as a place-event. The understanding of relational space comes from human geography, which also proposes a new ontology of the city, as outlined in Cities: Reimagining the Urban (2002) by Ash Amin and Nigel Thrift. According to these authors, what continously happens in a city is life, made up of countless human and non-human activities, communication, networks and communities. One form of community, they argue, is everyday life itself, in which unpredictable human connections and their effects are realised. The paper argues that, in “Rational Decisions”, the narration creates a new mode of Lithuanian urban literature, in which urban space is written / produced as a place-as-event of everyday life. The concept of ‘domestic disorder’ used in this essay could be one of the concepts sought by the new urban theory to bring research closer to the reality of the contemporary city.